Republic of Equatorial Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This note analyzes the medium- and long-term prospects of the hydrocarbon sector as a source of growth. Substantial hydrocarbon and financial reserves implies a sizable upward shift in the sustainable expenditure path. Rather than suggesting a specific fiscal rule, four simple alternatives are simulated and their implications assessed in terms of the overall non-oil balance. Comparing cross-country experiences with the current set up in Equatorial Guinea and statistical data on economic indices of Guinea have also been presented in the paper.